2015
DOI: 10.1083/jcb.20140808804292015c
|View full text |Cite
|
Sign up to set email alerts
|

The yeast ERAD-C ubiquitin ligase Doa10 recognizes an intramembrane degron

Abstract: Figure 4. Investigation of Sbh1/Sbh2 chimeric proteins. Both Sbh2 TM and ER-luminal regions contribute to the degron. (A) Schematic representation of Sbh1, Sbh2, and Sbh1/Sbh2 chimeric proteins used in this study. Sbh1-derived regions are depicted in light blue, and Sbh2-derived regions are shown in black. The nomenclature for Sbh1/Sbh2 chimeric proteins is as follows: "Sbh-XYZ" designates a chimeric protein in which the number at position X indicates the source of the cytosolic domain ("1": Sbh1; or "2": Sbh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…This suggests that Sbh1 could be dissociated from the Sec61 complex under lipid bilayer stress which leads to its premature degradation. This is consistent with the finding that Sbh2, the paralogue of Sbh1, becomes destabilised and rapidly degraded when unbound to the Sec61-like complex Ssh1 50 . Similarly, Sbh1 was found to interact with proteins of the ERAD pathway under lipid bilayer stress (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that Sbh1 could be dissociated from the Sec61 complex under lipid bilayer stress which leads to its premature degradation. This is consistent with the finding that Sbh2, the paralogue of Sbh1, becomes destabilised and rapidly degraded when unbound to the Sec61-like complex Ssh1 50 . Similarly, Sbh1 was found to interact with proteins of the ERAD pathway under lipid bilayer stress (Fig.…”
Section: Resultssupporting
confidence: 92%
“…4a). The temperature-sensitive growth defect of the sbh1 Δ sbh2 Δ mutant at 38 °C can be rescued with either a functional Sbh1 or Sbh2 as previously reported 50 . Sbh1-HA, HA-Sbh1, and TF-C ub -Sbh1 were all sufficient to rescue the growth defect of the sbh1 Δ sbh2 Δ mutant, suggesting that Sbh1 is functional regardless of epitope tag position.…”
Section: Resultssupporting
confidence: 72%
“…Therefore, proteins that are beyond repair, such as terminally misfolded proteins, are first extracted from the ER by adenosine triphosphate–driven motors and targeted for proteasomal degradation through ER-associated degradation (ERAD). In yeast, where most of the ERAD components have been originally described, transmembrane protein complex including the ubiquitin ligases Hrd1p and Doa10p recognize misfolded proteins and tag them for degradation ( 22 , 23 ). Upon poly-ubiquitylation via the ERAD machinery, the AAA+ adenosine triphosphatase (ATPase) Cdc48p (p97 or valosin-containing protein in humans) drives extraction of the proteins from the ER into the cytosol, where it is subsequently degraded by the proteasome ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus exceptions to these rules may exist as more substrates are analyzed. Indeed, a recent report showed that Doa10p also recognizes a newly established ERAD substrate bearing a “degron” in the transmembrane region ( Habeck et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%